Exploring how teachers acquire content knowledge of marine and coastal issues to contextualize the natural science curriculum - Mbuyazwe, Vuyiswa (Rhodes University, Faculty of Education, Department of Education, 2011)
The transformation process in the South African curriculum has highlighted a need for teachers to change from being passive implementers of curriculum. They are required to interpret the curriculum, adapt materials and develop lesson plans that will be responsive in their own context. They are also required to use materials and mediate learning. This research explores teacher acquisition of content knowledge on marine and coastal issues and probes how teachers work with materials in the development of lesson plans to contextualize the curriculum. A participatory action research process engaged 3 teachers in a contextualizing process of curriculum development. I started to work with the teachers to adapt and re-develop coastal and marine resources to support learning in local context. The research developed in two phases. The first examined existing teacher knowledge of marine and coastal issues and probed how content was integrated into lesson planning. Teachers identified knowledge acquisition as the priority to enable them to work with the materials and curriculum in their context. The second phase set out to enhance teachers' knowledge of marine and coastal resources through workshops and field trips to improve the adaptation and use of materials. To document these processes and outcomes in the context of this study, I employed a range of data generation strategies including questionnaires, workshops and classroom observations, field notes, focus group discussion and the review of lesson plans, learners' work and materials used. All participants collaboratively discussed and reflected on the process, but I was responsible for the final interpretation presented here. This study showed that teachers are still entrenched in their normal practice of working with content as facts and definitions, the delivery of abstract propositions that is not aligned with the curriculum goals. The new curriculum required teachers to change their teaching practice by using materials to mediate learning in context. The data revealed a mismatch between teacher practices and what the curriculum required from them.
Keywords: Uncatalogued